2014
DOI: 10.1007/s10753-014-9847-8
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Fas and FasL Is Associated with Infectious Complications and Severity of Experimental Severe Acute Pancreatitis by Promoting Apoptosis of Lymphocytes

Abstract: This study investigated the relationship of Fas and Fas ligand (FasL) expression and apoptosis of lymphocytes in relation to the pathogenic immune response and infectious complications observed in experimental severe acute pancreatitis in mice. Forty male Balb/c mice were randomly divided into control, mild (MAP), and severe acute pancreatitis (SAP) groups. Overexpression of Fas/FasL messenger ribonucleic acid (mRNA) and protein was observed in spleen-derived lymphocytes in SAP (p < 0.01). Apoptosis of these r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 51 publications
1
15
0
Order By: Relevance
“…Gallstones (46%) were the most common aetiological factor for AP, followed by hypertriglyceridemia (30%), alcohol consumption (13%), and other unknown factors (11%). The median value for the Acute Physiology and Chronic Health Evaluation II (APACHE II) score for AP was 10.5 (IQR, [8][9][10][11][12][13][14][15][16][17], indicating relatively high severity. According to the revised Atlanta Classification, 3 patients with AP were classified as having mild AP, 24 as moderately severe AP, and 29 as severe AP.…”
Section: Study Population Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gallstones (46%) were the most common aetiological factor for AP, followed by hypertriglyceridemia (30%), alcohol consumption (13%), and other unknown factors (11%). The median value for the Acute Physiology and Chronic Health Evaluation II (APACHE II) score for AP was 10.5 (IQR, [8][9][10][11][12][13][14][15][16][17], indicating relatively high severity. According to the revised Atlanta Classification, 3 patients with AP were classified as having mild AP, 24 as moderately severe AP, and 29 as severe AP.…”
Section: Study Population Characteristicsmentioning
confidence: 99%
“…Apoptotic cell death is involved in the development of infectious complications during the early stage of AP. Lymphocytes are thought to be critical in mediating apoptosis during impairment of cellular immunity in AP [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Kataoka et al (2004) showed how important to study role of apoptosis in severe acute pancreatitis and how hard to make a clinical study in this field [13]. The obtained data about the correlations between severity of acute pancreatitis and lymphocytes apoptosis intensity in peripheral blood coheres with multiple findings in this field, such as Qin et al [14] findings and experimental findings by Pinhu et al [15], and Weis et al [16].…”
Section: Discussionmentioning
confidence: 59%
“…Takeyama et al (2000) found that the main reason for depletion of lymphocytes in AP was apoptosis by cell cycle analysis. They showed that the proportion of apoptotic cells was nearly one quarter of total lymphocytes after incubation for 24 h. Studies have indicated that reduced absolute lymphocytes may be associated with apoptosis via Fas/FasL signaling in CD8 + T cells (Qin et al, 2013;Pinhu et al, 2014). These findings strengthen the hypothesis of subsequent CARS in AP (Pinhu et al, 2014).…”
Section: Lymphopenia In Apmentioning
confidence: 78%
“…They showed that the proportion of apoptotic cells was nearly one quarter of total lymphocytes after incubation for 24 h. Studies have indicated that reduced absolute lymphocytes may be associated with apoptosis via Fas/FasL signaling in CD8 + T cells (Qin et al, 2013;Pinhu et al, 2014). These findings strengthen the hypothesis of subsequent CARS in AP (Pinhu et al, 2014). Additionally, depletion of circulating lymphocytes is due to migration of activated lymphocytes to the inflammatory site in vivo, such as the pancreas and lungs (Bhatia et al, 2005).…”
Section: Lymphopenia In Apmentioning
confidence: 84%